Oligonucleotides with conjugated dihydropyrroloindole tripeptides: base composition and backbone effects on hybridization. - Kutyavin, I V (1997)
The ability of conjugated minor groove binding (MGB) residues to stabilize nucleic acid duplexes was investigated by synthesis of oligonucleotides bearing a tethered dihydropyrroloindole tripeptide (CDPI3). Duplexes bearing one or more of these conjugated MGBs were varied by base composition (AT- or GC-rich oligonucleotides), backbone modifications (phosphodiester DNA, 2'-O-methyl phosphodiester RNA or phosphorothioate DNA) and site of attachment of the MGB moiety (5'- or 3'-end of either duplex strand). Melting temperatures of the duplexes were determined. The conjugated CDPI3 residue enhanced the stability of virtually all duplexes studied. The extent of stabilization was backbone and sequence dependent and reached a maximum value of 40-49 degrees C for d(pT)8. d(pA)8. Duplexes with a phosphorothioate DNA backbone responded similarly on CDPI3 conjugation, although they were less stable than analogous phosphodiesters. Modest stabilization was obtained for duplexes with a 2'-O-methyl RNA backbone. The conjugated CDPI3 residue stabilized GC-rich DNA duplexes, albeit to a lesser extent than for AT-rich duplexes of the same length.